Peak heart rates and sympathetic function in tetraplegic nonathletes and athletes - Currie, K. D.; West, C. R.; Hubli, M.; Gee, C. M.; Cameron, M.; Krassioukow, A. V. (Medicine & Science in Sports & Exercise, 2015)
Purpose: To examine differences in peak heart rate (HR) and measures of sympathetic function between nonathletes and athletes with chronic, motor-complete, cervical spinal cord injury (SCI).